Crossing the Line: A Quantitative Analysis of Inmate Boundary Violators in a Southern Prison System - Dial, Kelly Cheeseman (American journal of criminal justice, 2008)
The majority of current research on inappropriate relationships between correctional staff and inmates involves a qualitative approach. This study sought to provide a quantitative analysis of these boundary violators by self-report data, which was provided by male inmates in a southern prison system. Building upon research by Allen and Bosta ( Games criminals play . Susanville, CA: Rae John Publishers, 1981) and Marquart et al. (Justice Quarterly 18:877–910, 2001) the inmates were divided into two distinct categories: Inmates who indicated “No relationship”, and those inmates who were “boundary violators”. This study examined the differences between these two categories utilizing demographic characteristics, custody level, and attitudes and prison behavior. Significant differences were found in boundary violator attitudes about female correctional officers and the behavior they exhibit in the presence of females.